Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1095/biolreprod.113.111823
|View full text |Cite
|
Sign up to set email alerts
|

How the Kidney Is Impacted by the Perinatal Maternal Environment to Develop Hypertension1

Abstract: Environmental conditions during perinatal development such as maternal undernutrition, maternal glucocorticoids, placental insufficiency, and maternal sodium overload can program changes in renal Na(+) excretion leading to hypertension. Experimental studies indicate that fetal exposure to an adverse maternal environment may reduce glomerular filtration rate by decreasing the surface area of the glomerular capillaries. Moreover, fetal responses to environmental insults during early life that contribute to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
124
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(127 citation statements)
references
References 136 publications
(233 reference statements)
3
124
0
Order By: Relevance
“…Oxidative stress has been reported to play a role in renal programming of the offspring [2][3][4]. We also reported that ADMAinduced NO/reactive oxygen species (ROS) imbalance is involved in the development of hypertension in several programming models [6][7][8][9][10].…”
Section: Adma and Oxidative Stressmentioning
confidence: 89%
See 3 more Smart Citations
“…Oxidative stress has been reported to play a role in renal programming of the offspring [2][3][4]. We also reported that ADMAinduced NO/reactive oxygen species (ROS) imbalance is involved in the development of hypertension in several programming models [6][7][8][9][10].…”
Section: Adma and Oxidative Stressmentioning
confidence: 89%
“…Early-life environmental insults during critical periods of kidney development can elicit epigenetic alterations, morphological changes and functional adaptations, leading to metabolic syndrome and related disorders in adult life [2][3][4]. Despite the rising incidence of maternal obesity, little attention has been paid to maternal fructose-intake-induced permanent changes in renal structure and function in the offspring, referred to as renal programming [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, oxidative stress has been implicated in fetal programming [7] and several studies in animal models of IUGR have evidenced that oxidative damage is present in key organs for cardiovascular control such as the heart [8] the kidney [9] [10] and blood vessels [11]. However, the presence of oxidative damage in animals with already established pathology does not determine whether oxidative stress is the cause or consequence of the cellular alterations [12].…”
Section: Introductionmentioning
confidence: 99%